Evaluation of nutritional composition, characterization and correlation of pulp quality parameters of cocoa (Research, Society and Development, 2022)
The objective of this work was to evaluate the nutritional composition, to characterize and to correlate the quality parameters of the pulp of cacao. The sample analyzed was the pulp of two cocoa fruits, two genotypes CCN51 and CEPEC 2005, commercially called blend. Approximate centesimal composition, caloric value, physical, chemical and physical-chemical characteristics and correlation of the analyzed parameters were evaluated. The pulp showed low caloric value (56.19 Kcal), high content of soluble solids (20.40ºBrix), ratio (32.45) and potassium (128.61mg/100g). In addition to very strong (r±0.91 to ±1.00) and strong (r±0.71 to ±0.90) correlations at the 5% level of significance between the ratio characteristics, soluble solids, Aw, total sugars, starch, density and vitamin C. The sample it presentes potential for use for development of food products, as it contains an important centesimal composition, expressive results for the soluble solids content, ratio, total and reducing sugars and relatively low caloric value, and can be added in diets, food supplementation, as well as in technological processing.